2017
DOI: 10.1038/s41598-017-10184-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of icosahedral PdxAg13−x (x = 0–13) clusters

Abstract: In this article, we present a modified Velocity-Verlet algorithm that makes cluster system converge rapidly and accurately. By combining it with molecular dynamics simulations, we develop an effective global sampling method for extracting isomers of bimetallic clusters. Using this method, we obtain the isomers of icosahedral PdxAg13−x (x = 0–13). Additionally, using the first-principle spin-polarized density functional theory approach, we find that each isomer still retains its icosahedral structure because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…also revealed that the base oil was sufficient for the friction reduction performance of a‐C‐coated surface. However, commercially available oils are commonly designed for the ferrous surface rather than the a‐C surface, and most previous efforts mainly focused on the anti‐friction improvement of inorganic and organic additives incorporated into fluid lubricants. The interaction between the a‐C and base oil at the sliding interface and its dependence on base oil variety are still not well understood, and the underlying friction mechanism in synergism is also not clear due to the complexity of structural evolution of friction interface in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…also revealed that the base oil was sufficient for the friction reduction performance of a‐C‐coated surface. However, commercially available oils are commonly designed for the ferrous surface rather than the a‐C surface, and most previous efforts mainly focused on the anti‐friction improvement of inorganic and organic additives incorporated into fluid lubricants. The interaction between the a‐C and base oil at the sliding interface and its dependence on base oil variety are still not well understood, and the underlying friction mechanism in synergism is also not clear due to the complexity of structural evolution of friction interface in experiment.…”
Section: Introductionmentioning
confidence: 99%
“…[107,108] It is well known that titanium hydroxide and/or titania show good photocatalytic activities. [109,110] The surfaces of M n+1 X n layers bond O and OH groups, thus MXenes may also possess good photocatalytic activity. [111] It has been reported that organic particles can be dissociated by MXene under specific light conditions, and Ti 2 C can separate oxygen into individual O atoms, which confirms the photocatalytic activity of MXenes.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…In addition, some bimetallic clusters or their ionic states, such as MAl4 − (M = Li, Na, Cu) and XAl3 -(X = Si, Ge, Sn, Pb) exhibit the aromatic property [18,19] and this extends the concept of aromaticity to metal clusters. The magnetism and stability of metal clusters can be tuned by doping transition metal elements, which are characterized by a partially filled d shell [20][21][22][23][24]. It is thus expected that transition metal doping into aluminum clusters will yield clusters possessing the novel physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%